Additions to the Flora of Singanallur Lake, An Urban Wetland From Coimbatore, Tamil Nadu, India - Karthik, B.; Kunhikannan, C.; R. Peter, Vinny; Joseph Reginald, L. (Indian Forester, 2026)
The present study is aimed to document the floristic wealth of Singanallur lake, Coimbatore, Tamil Nadu, India, which was declared as “Urban Biodiversity Conservation Zone” by Coimbatore City Municipal Corporation in 2017. Intensive botanical explorations were conducted in the lake between January 2023 and December 2024 and the study resulted in documentation of 121 flowering plants which were additions to the existing flora of 453 species; therefore, a total of 574 species of plants were recorded from the region. Of the observed additional plants, three endemics species such as, Dicliptera cuneata with a population of c. 200 plants, a steno-endemic and threatened plant, Cordia diffusa / Kovai Manjack with 12 individuals and Viscum subracemosum with 10 individuals were observed from the region. The list of observed plants along with family, habit and its uses were provided and the medicinal plants constituted for 78% of the recorded list.